THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND COMPENSATION ON EMPLOYEE PERFORMANCE DIMEDIATION OF WORK SATISFACTION AT PT. TOR GANDA - Venna Natala Lingga; Prihatin Lumbanraja; Meilita Tryana Sembiring (RADJA PUBLIKA, 2023)
This study aims to identify the influence of transformational leadership style and compensation on employee performance mediated by job satisfaction at PT. TOR GANDA. The number of samples in this study were 92 respondents who were determined using simple random sampling. The type of data used is associative research. Research connects causation or causation. which analyzes the independent variables, mediating variables and dependent variables that are affected. Data analysis used a simple linear regression equation with the SPSS 2023 tool. The results showed that Transformational Leadership had an effect on Job Satisfaction at PT. TOR GANDA, Compensation affects Job Satisfaction at PT. TOR GANDA, Transformational Leadership influences Employee Performance at PT. TOR GANDA, Compensation affects Employee Performance at PT. TOR GANDA, Job Satisfaction affects Employee Performance at PT. TOR GANDA, Transformational Leadership influences Employee Performance through Job Satisfaction at PT. TOR GANDA and Compensation affect Employee Performance through Job Satisfaction at PT. TOR GANDA.